Halal assurance system training and its implementation with the Muhammadiyah halal pledge - Mahfudh, Nurkhasanah; Ikawati, Retty; Salamah, Nina; Ahda, Mustofa (Community Empowerment, 2021)
The implementation of Law Number 33 of 2014 concerning Halal Product Guarantee requires all products circulating in Indonesia to have a halal certificate. Micro businesses must also keep up with these developments. The 2020 Job Creation Law states that the obligation to be halal certified is based on statements from micro and small business actors. Muhammadiyah responded to this scheme by setting a halal pledge for micro and small businesses. To support the statement of the halal pledge which is based on understanding, training activities and assistance for the halal production process are carried out for micro and small businesses. The results of this activity revealed a significant increase in the understanding of MSMEs with an average pre-test score of 36 Â± 6.9 and an average post-test score of 72 Â± 14.1. In addition, participants were also able to compile the Muhammadiyah halal pledge application form.